Research Status of Friction Interface Evolution Mechanism of Non-magnetic Steel - Xue, Tiantian (International Journal of Mechanical and Electrical Engineering, 2024)
The non-magnetic drill pipe (composed of male and female thread joints and rod bodies) is the key component of the directional drilling technology equipment for gas extraction in coal mine tunnels. The thread joint and the drill pipe body are connected by continuous drive friction welding. In the study, it was found that the banded structure appeared in the joint of continuous drive friction welding of non-magnetic steel, which reduced the strength of drill pipe. At the same time, it is found that the heat flow mode is one of the key factors affecting the banded structure, and the heat flow mode is based on the evolution of the interface plastic ring. In this paper, through the review of the research status of the interface evolution law of non-magnetic steel continuous drive friction welding, the experimental method for the study of the interface evolution law of non-magnetic steel continuous drive friction welding is found.